1998
DOI: 10.1093/bja/80.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remifentanil on the haemodynamic response to orotracheal intubation

Abstract: We have examined the effect of remifentanil on the haemodynamic response to orotracheal intubation in a randomized, double-blind study. We studied 40 patients allocated to one of four groups of 10 each, to receive the following immediately before induction of anaesthesia: remifentanil 1 microgram kg-1 bolus over 30 s, followed by an infusion of 0.5 microgram kg-1 min-1; saline placebo only; glycopyrrolate 200 micrograms and remifentanil 1 microgram kg-1 bolus over 30 s, followed by an infusion of 0.5 microgram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
9

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(86 citation statements)
references
References 12 publications
3
71
1
9
Order By: Relevance
“…These findings are in agreement with adult studies, which demonstrated significant decreases in MAP when higher doses of remifentanil were used either as a bolus or continuous infusion. 17,18 The decrease in CBFV prior to tracheal intubation seemed to coincide with a decrease in MAP in the present study, suggesting that remifentanil may be associated with impaired cerebral blood pressure autoregulation. Alternatively, remifentanil may have decreased MAP to pressures below the lower limit of cerebral autoregulation.…”
Section: Objectifsupporting
confidence: 59%
“…These findings are in agreement with adult studies, which demonstrated significant decreases in MAP when higher doses of remifentanil were used either as a bolus or continuous infusion. 17,18 The decrease in CBFV prior to tracheal intubation seemed to coincide with a decrease in MAP in the present study, suggesting that remifentanil may be associated with impaired cerebral blood pressure autoregulation. Alternatively, remifentanil may have decreased MAP to pressures below the lower limit of cerebral autoregulation.…”
Section: Objectifsupporting
confidence: 59%
“…Without a concurrent anticholinergic agent remifentanil was associated with bradycardia or hypotension, or both, in 30-50% of healthy patients during anesthetic induction and intubation. 10,11,28 On this basis, we considered the administration of an anticholinergic agent necessary, which might have contributed also to the observed stability of heart rate in our study in contrast to the results obtained without using an anticholinergic agent. In the present study, the cardiovascular intubation response was totally prevented in the groups receiving 2 or 4 µg·kg -1 remifentanil.…”
Section: Discussionmentioning
confidence: 94%
“…A variety of interventions [1][2][3][4][5][6] have been examined as possible stabilisers of the cardiovascular response, but none of these interventions have resulted in stable induction of anaesthesia because of either the inadequacy of their effect or unwanted sideeffects. It would be of great help if we could predict the haemodynamic response to induction of general anaesthesia.…”
mentioning
confidence: 99%